Handbook of plastics joining : a practical guide. (PDL handbook series., 1997)
A hands-on guide to choosing and using old and new technologies for joining plastics and elastomers. Includes discussions of over 25 techniques used to join plastics to themselves and to other materials. Advantages and disadvantages of each technique along with discussions of applications are presented. This book is a resource for novice and expert alike in determining the best joining technique for their application and providing guidance in how to design and prepare for production.